Answer:
D. [tex] = \frac{b}{a} [/tex]
Step-by-step explanation:
Given:
[tex] \frac{b^{-2}}{ab^{-3}} [/tex]
Required:
Assuming a ≠ 0, b ≠ 0, find the expression equivalent to the given expression.
SOLUTION:
[tex] \frac{b^{-2}}{ab^{-3}} [/tex]
Recall the exponent rule => [tex] \frac{x^{a}}{x^{b}} = x^{a - b} [/tex]
Applying the exponent rule, we would have:
[tex] \frac{b^{-2 -(-3)}}{a} [/tex]
[tex] = \frac{b^{-2 + 3}}{a} [/tex]
[tex] = \frac{b^{1}}{a} [/tex]
[tex] = \frac{b}{a} [/tex]
Thus, the equivalent expression of [tex] \frac{b^{-2}}{ab^{-3}} [/tex] = [tex] \frac{b}{a} [/tex]